LAZARUS 1 functions as a positive regulator of plant immunity and systemic acquired resistance - Chen, Yue; Han, Yue; Huang, Weijie; Zhang, Yanjun; Chen, Xiaoli; Li, Dongyue; Hong, Yi; Gao, Huhu; Zhang, Kewei; Zhang, Yuelin; Sun, Tongjun (Frontiers in Plant Science, 2024)
Systemic acquired resistance (SAR) is activated by local infection and confers enhanced resistance against subsequent pathogen invasion. Salicylic acid (SA) and Nhydroxypipecolic acid (NHP) are two key signaling molecules in SAR and their levels accumulates during SAR activation. Two members of plant-specific Calmodulin-Binding Protein 60 (CBP60) familytranscription factor family, CBP60g and SARD1, regulate the expression of biosynthetic genes of SA and NHP., . CBP60g and SARD1 function as master regulators of plant immunity and their expression levels are tightly controlled. Although there are numerous reports on regulation of their expression, the specific mechanisms by which SARD1 and CBP60g respond to pathogen infection are not yet fully understood. This study identifies and characterizes the role of the LAZ1and its homolog LAZ1H1 in plant immunity. Through aA forward genetic screen was conducted in the sard1-1 mutant background to, the sard6-1 mutant was identifyied ,mutants with enhanced SAR-deficient phenotypes (sard mutants), leading to the discovery of sard6-1, which maps to the LAZ1 gene. LAZ1 and its homolog LAZ1H1 were found to be positive regulators of SAR through regulating the expression of CBP60g and SARD1 as well as biosynthetic genes of SA and NHP. Furthermore, Overexpression of LAZ1, LAZ1H1 and its homologs from Nicotiana benthamiana and potato enhanced resistance in N. benthamiana against Phytophthora pathogens. These findings indicate that LAZ1 and LAZ1H1 are evolutionarily conserved proteins that play critical roles in plant immunity.